PENERAPAN MODEL PEMBELAJARAN COOPERATIVE TYPE SCRIPT UNTUK MENINGKATKAN KECERMATAN DAN PRESTASI BELAJAR - Solihantri (UNIB Press, 2022)
In the era of globalization, it seems that learning programs have not been able to provide satisfactory results where students focus more passively on learning activities, this is due to the monotonous way of learning that is only receiving from a teacher and at the end of the lesson there is less emphasis on concluding learning. So that problems arise in learning such as tense and boring classes which ultimately affect student learning result. This study aimed at knowing the increase of students’ learning accuracy, students’ achievement and describing the effectiveness of the application of the cooperative type script learning model in the subjects of Akidah Akhlak of Grade X IPS students at MAN 1 Pagaralam. The research method used was School Action Research and Quasi-Experimental. The subjects of this study were 36 students of Grade X IPS students of MAN 1 Pagaralam. Data collection techniques were through observation, documentation studies, questionnaires and test questions, while data analysis and interpretation was carried out by tracking processes, field notes, other materials and Different Tests (t-test) of Quasi-Experimental Research (Wilcoxon). The results showed that the application of the cooperative type script learning model can improve the students’ learning accuracy and learning achievement in the very good category, and the cooperative type script learning model in the Akidah Akhlak subject was more effective in increasing the accuracy of learning and students’ achievement compared to conventional methods, so that there was a significant difference in the results of learning accuracy and students’ achievement before and after the implementation of the cooperative type script learning model. The application of this learning model encouraged the change in perception to meet the demands of active, creative, effective, fun, innovative, happy and quality learning.